THE CRUELTY OF BURMESE MILITARY REGIME IN SYLVESTER STALLONE'S RAMBO IV (2008): A MARXIST APPROACH - FAHRIANI, IRMA (2011)
This study is about cruelty in Rambo IV movie (2008). This objective of the study is to apply the marxist approach to analyze the cruelty in stallone's Rambo IV. The writer uses Rambo's major point of Marxist to answer the problem of the study. The study is descriptive qualitative research that the data are taken from script of Rambo IV. The technique of the collecting data is library research, while the technique of analyzing data is descriptive. Having analyzed this movie, the writer draws the results of the study. First, based on the structural analysis the director successfully delivers the moral message through the excellent unity of structural element. The director wants to say that everyone in the world has the similar right. The movie reflects the oppression. Second, based on the Marxist analysis human has different view, their views are based on dialectical materialism, historical materialism, alienation, class struggle and revolution. Rambo's struggle is meaningful when he has a good action to show his power to get the peace.